Strategic Information Systems Planning: A Case of Bank Rakyat - Adnan, Azman (2000)
The impact of computerisation comes in many different ways, with organisations having various perception towards the technology. Some perceive it as keeping up with the trend and thus the subject matter becomes less cost effective or may even be a costly project to pursue. Organisation such as these are merely replacing their traditional typewriters with personal computers thus under utilising the strength of computers. Productivity, on the other hand equals to output over the input and based on this equation, one may easily conclude that in order to increase productivity, either the output is increased or the input reduced. It is concluded in this study that by further exploiting the Information Technology (IT) potentials and constructing a Strategic Information Systems Planning (SISP) model, it would help an organisation to optimise its information resources thus achieving its goals i.e., to create efficiency and reduce input resources which will therefore increase productivity and profitability. However, the expectation of an organisation towards IT to achieve its goals may lead to two different paths i.e., success or failure in the implementation. It is not uncommon to hear of failures in the implementation of IT projects and in such cases, costs incurred has been considered a waste that discourages the organisation to proceed further in the implementation of lT projects and it is not impossible for these organisations to revert to their traditional methods of operations. Therefore, before the IT potentials could further be exploited, the problem of IT illiteracy also being a distracting factor to the implementation of computerisation, should initially be eliminated or greatly reduced. This especially refers to the higher level management for better understanding of the benefits that could be achieved. This research proves that the implementation of IT projects could yield better results with the consideration that the basic issues are not neglected and attended to in a much suitable approach. Suitability of the approach refers to the tools of automation introduced, to obtain better results that may lead to a higher percentage of success in the implementation and thus leads to the achievement of the organisation's goals. At the end of this research, a model is constructed which may be used by other organisations with similar nature of situation and issues.